Composite lay-up configuration effect on double and single sided bonded patch repairs - Toufik Achour; Fayal Mili (Fracture and Structural Integrity, 2022)
Understanding the failure modes of damaged or cracked structures and repaired by bonding a composite patch is an essential point to improve its resistance to failure and subsequently extend its service life. In the present study, a 3D finite element analysis using ANSYS software was performed to elucidate the failure modes of the repaired structures by double and single sided bonded composite. The plate is represented by an aluminum plate (Al2024 T3), cracked at the edge and repaired by three types of laminates, with different fiber orientation in order to determine its effect on the repair. The contact interfaces patch-adhesive and aluminum-adhesive were modeled by cohesive zone modeling (CZM) using bilinear interface of delamination (BID) method to determine the failure at the adhesive layer. The obtained results show the importance of the impact of the composite patch fiber orientation on the structure design for suitable repair